Students’ Writing Anxiety in Learning English as a Foreign Language - Putra, I Komang Janu Prianda; Padmadewi, Ni Nyoman; Ratminingsih, Ni Made (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
This research aimed to investigate the writing anxiety experienced by eleventh-grade students in learning English as a Foreign Language (EFL) in Bali. By conducting a quantitative research method, this research involved 76 students as the participant of the study. The research employed an adapted questionnaire from Cheng (2004), consisting of 27 designed statements. The result revealed that many students face challenges with writing anxiety in English. The findings showed that linguistic challenges, such as concerns about using expressions and sentence patterns incorrectly, and time constraints like feeling stressed under time pressure, significantly contribute to writing anxiety. Additionally, the positive aspect of the study demonstrated that students actively work to minimize mistakes in their writing, emphasizing the importance of accuracy in managing writing anxiety which may imply the motivation to learn English.